Analysis of the Influence of Make-up Spending, Income Sources, and Self-reward Habits on Generation Z’s Interest in Saving Money - Maharani Zahara, Dienisa Etka; Haeni, Intan Nur; Widianingsih, Tiara (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
The habit of saving money has emerged because many members of Generation Z face financial problems influenced by a consumptive lifestyle, especially in terms of beauty and self-satisfaction. This study aims to analyze the influence of makeup spending, income sources, and self-reward habits on the interest in saving among Gen Z, as well as to identify consumption patterns related to self-control and financial inclusion levels. This study uses a quantitative approach with an online questionnaire distributed through social media. The results show that makeup spending has a negative effect on interest in saving due to social trends. Income sources have a positive effect, although low financial inclusion limits access to financial instruments. Self-reward habits decrease interest in saving, although self-control and financial literacy can moderate this negative effect. Peer influence reinforces consumptive behavior, while good financial literacy increases the willingness to save. These findings are in line with studies on pocket money, lifestyle, self-control, and repeated makeup purchases.